Jenkins 2.x continuous integration cookbook : over 90 recipes to produce great results using pro-level practices, techniques, and solutions /: over 90 recipes to produce great results using pro-level practices, techniques, and solutions. (2017) - Soni, Mitesh; Berg, Alan Mark
No abstract available